Analysis of Pulmonary Tuberculosis Incidence in Productive Age and Family Role in its Management: Literature Review - Ichea Irawan; Satrina; Marniati (International Journal of Psychology and Health Science, 2025)
Tuberculosis (TB) is an infectious disease that remains a major health problem in Indonesia, particularly among productive age groups. This study aims to analyze various factors influencing the incidence of pulmonary TB in productive age and review the role of families in its management. The method used is a literature review of 30 national scientific articles published between 2017 and 2024. The review results show that internal factors such as knowledge, attitude, motivation, nutritional status, and treatment adherence play important roles in TB control. External factors such as home ventilation, housing density, socioeconomic conditions, and family support also significantly influence TB incidence and management. Family support has been proven to strengthen patients' positive behaviors, including undergoing treatment and implementing Clean and Healthy Living Behaviors (PHBS). Therefore, TB control requires a multidimensional approach involving educational interventions, environmental quality improvement, and cross-sector collaboration between healthcare workers, families, and communities.Tuberculosis (TB) is an infectious disease that remains a major health problem in Indonesia, particularly among productive age groups. This study aims to analyze various factors influencing the incidence of pulmonary TB in productive age and review the role of families in its management. The method used is a literature review of 30 national scientific articles published between 2017 and 2024. The review results show that internal factors such as knowledge, attitude, motivation, nutritional status, and treatment adherence play important roles in TB control. External factors such as home ventilation, housing density, socioeconomic conditions, and family support also significantly influence TB incidence and management. Family support has been proven to strengthen patients' positive behaviors, including undergoing treatment and implementing Clean and Healthy Living Behaviors (PHBS). Therefore, TB control requires a multidimensional approach involving educational interventions, environmental quality improvement, and cross-sector collaboration between healthcare workers, families, and communities.